Exploring Peltier effect in organic thermoelectric films - Jin, Wenlong (2018)
Organic materials are emerging thermoelectric candidates for flexible power generation and solid-cooling applications. Although the Peltier effect is a fundamental thermoelectric effect that enables site-specific and on-demand cooling applications, the Peltier effect in organic thermoelectric films have not been investigated. Here we experimentally observed and quasi-quantitatively evaluated the Peltier effect in a poly(Ni-ett) film through the fabrication of thermally suspended devices combined with an infrared imaging technique. The experimental and simulation results confirm effective extraction of the Peltier effect and verify the Thomson relations in organic materials. More importantly, the working device based on poly(Ni-ett) film yields maximum temperature differences as large as 41 K at the two contacts and a cooling of 0.2 K even under heat-insulated condition. This exploration of the Peltier effect in organic thermoelectric films predicts that organic materials hold the ultimate potential to enable flexible solid-cooling applications.